Developing business models for a circular bioeconomy: the B2Circle tool - Salvador, Rodrigo (2021)
Background. The circular bioeconomy (CBE) is a solution to the current linear (takemake-use-dispose) state of many businesses and the increasing generation of waste. In a CBE, biological resources are used to make products of high added value using more circular practises, which products might be novel or serve to replace those currently made from non-renewable sources. Nonetheless, CBE systems need welldesigned business models to succeed. Purpose. The objective of this dissertation was to develop a self-assessment tool to assist bioeconomy businesses in adopting and taking advantage of a more circular conduct by suggesting a business model to be pursued. Novelty. The novelty of the present dissertation lies in identifying business models for a circular bioeconomy (BMCBE) and proposing a tool to recommend a BMCBE to bioeconomy businesses. Design/methodology/approach. This research was structured in three Phases. In Phase I, a systematic literature review and a practise review using semi structured interviews were conducted to identify the barriers, challenges, drivers, and opportunities for businesses in a CBE, and to propose a taxonomy for BMCBEs. In Phase II a Delphi study, using Fuzzy Analytic Hierarchy Process (FAHP), assisted by specialists from both academia and industry allowed to validate a set of criteria to determine the characteristics of the BMCBEs and use those criteria to profile the BMCBEs in the proposed taxonomy. A method using the theory of Euclidean distance was also proposed to enable comparing the characteristics of the business model of an organisation that uses the tool with those of the seven BMCBEs. Phase III comprised the testing of the proposed tool. Findings. The proposed taxonomy included seven BMCBEs: Optimising resource efficiency and use; Establishing biorefineries; Value recovery from waste; Resource exchange; Innovation towards bio- and renewable resources; Valuing the local economy, and; Service- and result-oriented offers. A set of 19 criteria were used to profile the seven BMCBEs, and the results of such profiling composed the basis of the proposed tool, named B2Circle. Organisation X was invited to be first user of the tool, to whom the tool recommended the BMCBE “Establishing biorefineries”. This has been validated with Organisation X and opportunities to further develop their business model were discussed. Research implications. The B2Circle tool aims to point a path that can bridge the gap between the current state and the recommended circular business model for an organisation. It is intended as a first step towards greater circularity in bioeconomy businesses, enlightening businesses towards establishing a CBE while accounting for their business approach.